MODEL LOW ALKALI ACTIVATOR GEOPOLYMER CONCRETE MATERIAL RATIO WITH COMPRESSIVE STRENGTH - Eri Setia Romadhon; Antonius; Sumirin (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
This paper presents the results of research on the relationship between the ratio of the composition of low alkaline activator geopolymer concrete and compressive strength. The main objective of this research is to develop a relationship model of the ratio of the constituent materials of low alkaline activator geopolymer concrete with compressive strength. The variables reviewed were the amount of alkaline activator 4% low enough, room temperature treatment and 60oC ratio of alkaline activator/fly ash (AAS/FA) namely 0.35, 0.4, 0.5, 0.6. The test results show that the mole ratios of the main ingredients for geopolymer concrete are low in alkaline activators SiO2/Al2O3, Na2O/SiO2 and H2O/Na2O in accordance with the mole ratio specifications for geopolymer concrete ingredients developed by Subaer Junaedi. The relationship model for the mole ratio of the constituent materials of low geopolymer concrete activator 4% and 5% curing at room temperature and 60°C with compressive strength shows a non-linear or exponential relationship with a correlation number close to 1, valid.